2014
DOI: 10.1073/pnas.1411755111
|View full text |Cite
|
Sign up to set email alerts
|

Relating influenza virus membrane fusion kinetics to stoichiometry of neutralizing antibodies at the single-particle level

Abstract: The ability of antibodies binding the influenza hemagglutinin (HA) protein to neutralize viral infectivity is of key importance in the design of next-generation vaccines and for prophylactic and therapeutic use. The two antibodies CR6261 and CR8020 have recently been shown to efficiently neutralize influenza A infection by binding to and inhibiting the influenza A HA protein that is responsible for membrane fusion in the early steps of viral infection. Here, we use single-particle fluorescence microscopy to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(116 citation statements)
references
References 45 publications
16
99
1
Order By: Relevance
“…Strain-specific neutralization of G-specific antibodies correlates with epitope specificity. Antibody efficacy is determined by multiple variables, ranging from antibody and target glycosylation, binding on and off rate, the epitope, and the angle that the target is approached by the antibody (4,(22)(23)(24). Here, we hypothesized that for the G-specific antibodies, the neutralization potency may be determined by the binding site on the G protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain-specific neutralization of G-specific antibodies correlates with epitope specificity. Antibody efficacy is determined by multiple variables, ranging from antibody and target glycosylation, binding on and off rate, the epitope, and the angle that the target is approached by the antibody (4,(22)(23)(24). Here, we hypothesized that for the G-specific antibodies, the neutralization potency may be determined by the binding site on the G protein.…”
Section: Resultsmentioning
confidence: 99%
“…Fc tail presentation could also play a role during other immune effector functions activated through bound antibodies, such as antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) of infected cells, as has been shown in influenza disease (24). Some of our antibodies were able to induce substantial ADCC (mainly epitopes B [AT34] and C [AT40 and AT50]), while others were more potent inducers of ADCP (mainly epitope D, AT32 and AT33).…”
Section: Discussionmentioning
confidence: 99%
“…When the number of inhibited HAs is sufficiently large to prevent the formation of a fusogenic cluster, the particle will fail to achieve hemifusion altogether ( Figure 4G right and H rightmost). The presence of such time delay and concomitant reduction in fusion yield at intermediate inhibition levels was experimentally demonstrated [113].…”
Section: Hemifusion Is Abrogated At Sub-stoichiometric Levels Of Bounmentioning
confidence: 95%
“…Drugs targeting the conserved HA stem or extended intermediate seem particularly promising in finding a universal influenza therapy. A single-particle assay using antibodies and antibody fragments that bind the stem of the HA trimer in the prefusion state and prevent the low-pH conformational change showed the effect of inhibiting fusion-competent HAs one by one [113]. By counting the number of antibodies bound per individual virion and observing the resulting fusion yield, it was found that not all HA trimers need to be inhibitor-bound to fully abrogate fusogenicity, supporting the idea that hemifusion requires a network of HAs that can form a cluster ( Figure 4B left).…”
Section: Hemifusion Is Abrogated At Sub-stoichiometric Levels Of Bounmentioning
confidence: 99%
See 1 more Smart Citation